Adsorbed states of iron(II) phthalocyanine on Ag(111) studied by high‐resolution electron energy loss spectroscopy. (15th May 2014) - Ohta, Naoka; Arafune, Ryuichi; Tsukahara, Noriyuki; Takagi, Noriaki; Kawai, Maki; Yurimoto, Hisayoshi
<x xml:space="preserve">Abstract</x> We investigated the adsorption states of iron(II) phthalocyanine (FePc) molecules on Ag(111) by using high‐resolution electron energy loss spectroscopy (HREELS). The HREELS spectra were taken as a function of the coverage of FePc. At 1 monolayer, vibrational modes assigned as A2u and A1g representations were observed mainly by the dipole scattering mechanism, which indicates that the first‐layer molecules adsorb with the molecular planes parallel to the surface. The vibration associated with the motion of the central Fe2+ ion perpendicular to the molecular plane shows a considerable shift of the vibration energy. This reflects significant bonding interactions between the FePc molecule and the substrate. In the high coverage regime, multilayers were grown, and the vibration modes attributed to not only A2u but also Eu representation were observed. The FePc molecules in the upper layers tilt the molecular planes to the substrate. The vibrational energy is almost identical to those in the gas phase, indicating weaker interactions between the molecules. Copyright © 2014 John Wiley & Sons, Ltd.